Preventing Friction Induced Chondrocyte Apoptosis: A Comparison of Human Synovial Fluid and Hylan G-F 20 - Waller, Kimberly A (2012)
OBJECTIVES: Symptomatic osteoarthritis (OA) is a common painful disease with limited treatment options. A rising number of OA patients have been treated with intraarticular injections of hyaluronic acid, including the high molecular weight hylan G-F 20, which is injected following arthrocentesis. This study investigated the effectiveness of hylan G-F 20 to lower coefficient of friction (COF) and prevent chondrocyte apoptosis in vitro. METHODS: A disc-on-disc bovine cartilage bearing was used to measure the static and kinetic COF when lubricated with hylan G-F 20, human synovial fluid (HSF) and phosphate buffered saline (PBS). Following friction testing, we stained paraffin embedded sections of these cartilage bearings for activated caspase-3, a marker of apoptosis. RESULTS: Bearings lubricated with hylan G-F 20 had kinetic COF values that were similar to bearings lubricated with PBS, but significantly higher than those lubricated with HSF. There were no significant differences in static COF values in bearings lubricated with hylan G-F 20 as compared to PBS or HSF. However, bearings lubricated with HSF had a significantly lower static COF values compared to bearings lubricated with PBS. The mean percentage of caspase-3 positive chondrocytes in the superficial and upper intermediate zones of bearings lubricated with hylan G-F 20 were significantly higher when compared to bearings lubricated with HSF or unloaded controls, but significantly lower than those lubricated with PBS. CONCLUSION: These findings indicate that joint lubrication may prevent chondrocyte apoptosis by lowering the COF. Furthermore, removal of synovial fluid prior to hylan G-F 20 injection may be detrimental to cartilage health.